Den banala debatten: Hanna Arendt i Jerusalem - Lundgren, Svante (Nordisk judaistik/Scandinavian Jewish Studies, 2001)
Few books within the field of Jewish studies have caused so much anger and intense debate as Hannah Arendt’s Eichmann in Jerusalem. A Report on the Banality of Evil. The author was considered to be a self-hating Jew because she accused the Jewish leaders during the Holocaust for having complied with Nazi orders and thus having facilitated the mass murder. Her view of the personality of Eichmann was considered to be wrong, and her way of writing was seen as inappropriate in its lack of humility in dealing with an issue like the Holocaust. Although much of the critique was unfair, Arendt’s non-diplomatic style of writing contributed to the negative reactions.